Body Dysmorphic Symptoms Scale for patients seeking esthetic surgery: cross-cultural validation study - Ramos, Tatiana Dalpasquale; Brito, Maria José Azevedo de; Piccolo, Mônica Sarto; Rosella, Maria Fernanda Normanha da Silva Martins; Neto, Miguel Sabino; Ferreira, Lydia Masako (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: Rhinoplasty is one of the most sought-after esthetic operations among individuals with body dysmorphic disorder. The aim of this study was to cross-culturally adapt and validate the Body Dysmorphic Symptoms Scale. DESIGN AND SETTING: Cross-cultural validation study conducted in a plastic surgery outpatient clinic of a public university hospital. METHODS: Between February 2014 and March 2015, 80 consecutive patients of both sexes seeking rhinoplasty were selected. Thirty of them participated in the phase of cultural adaptation of the instrument. Reproducibility was tested on 20 patients and construct validity was assessed on 50 patients, with correlation against the Yale-Brown Obsessive Compulsive Scale for Body Dysmorphic Disorder. RESULTS: The Brazilian version of the instrument showed Cronbach’s alpha of 0.805 and excellent interrater reproducibility (intraclass correlation coefficient, ICC = 0.873; P < 0.001) and intra-rater reproducibility (ICC = 0.939; P < 0.001). Significant differences in total scores were found between patients with and without symptoms (P < 0.001). A strong correlation (r = 0.841; P < 0.001) was observed between the YaleBrown Obsessive Compulsive Scale for Body Dysmorphic Disorder and the Body Dysmorphic Symptoms Scale. The area under the receiver operating characteristic curve was 0.981, thus showing good accuracy for discriminating between presence and absence of symptoms of body dysmorphic disorder. Forty-six percent of the patients had body dysmorphic symptoms and 54% had moderate to severe appearancerelated obsessive-compulsive symptoms. CONCLUSIONS: The Brazilian version of the Body Dysmorphic Symptoms Scale is a reproducible instrument that presents face, content and construct validity.